Impact of Competency and Self-esteem on the Teacher Engagement at Jinja City Primary Schools, Uganda - Bamusibule, Charles; Kato, Joshua Kimata; Mugizi, Wilson; Kyozira, Peter; Muloopa, Haruna (East African Journal of Education Studies, 2024)
The study examined the relationship between teacher competence and engagement in Jinja city, mediated by self-esteem. Specifically, the study tested the influence of teacher competence on engagement and self-esteem, the influence of self-esteem on engagement, and the mediating effect of self-esteem on the relationship between teacher competence and engagement. Based on the three-component model by Khan (1990), engagement was studied in terms of vigour, dedication, and absorption. The study adopted a cross-sectional research design on a sample of 196 teachers in Jinja city. The study adopted a self-administered questionnaire to collect the data. Data analysis involved carrying out partial least squares structural equation modelling (PLS-SEM). The results indicated that teacher competence negatively and insignificantly influenced engagement, while teacher competence positively but insignificantly influenced self-esteem and self-esteem positively and significantly influenced engagement. The results also revealed that self-esteem partially mediated the relationship between teacher competence on engagement. The study concluded that while self-esteem is imperative for teacher engagement, teacher competence did not promote engagement and self-esteem. Therefore, it was recommended that to boost teacher engagement school administrators in Jinja City should promote teacher self-esteem compared to teacher competence